Cultural Village Management Model to Enhance Cultural Tourism in The Special Region of Yogyakarta - Anggarani Pribudi; Vina Dini Pravita; Supardal Supardal (International Journal of Social Service and Research, 2023)
One of the main elements in the Yogyakarta privilege/specialty policy is cultural development, including strengthening cultural villages as an integral part that supports Yogyakarta as a special region. In connection with the development of cultural villages, there is an opportunity to develop cultural tourism based on cultural villages that can be offered to both domestic and foreign tourists. In fact, there are still several problems with developing cultural villages. One of the problems is structural issues which are still dominant, considering that the cultural village was formed by the provincial government with various regulatory policies, and as a result, cultural villages are not given independence to manage themselves but rather are driven by the supra-village. Village dependency is also caused by the village's inadequacy to develop cultural tourism village so it needs guidance from the government and is far from being self-sufficient. This study uses an exploratory qualitative approach, by analyzing each model of a cultural village and its potential for developing cultural village-based cultural tourism. Data collection was carried out by in-depth interviews with government officials in charge of the cultural department and cultural stakeholders in the cultural villages. The results of the study show that the formation of several cultural village models has not resulted in cultural village-based cultural tourism. This is because cultural villages are more preoccupied with serving various policies from the cultural service and budget accountability given to cultural villages. Thus, cultural villages run out of energy to innovate in cultural events that can be offered to tourists. Furthermore, the limited human resources to manage cultural tourism in each village are also an important problem that still hinders the development of cultural tourism villages.